Performance Assessment of Banks listed on Tehran Stock Exchange based on CAMEL Indicators - Ebrahimi, Seyed Kazem; Bahraminasab, Ali; Fard, Maryam Yousefi (International Journal of Economics and Financial Issues, 2017)
Choosing efficient and appropriate approaches to assess bank’s financial performance is one of the most important issues having attracted bank analysts and researchers’ attention in recent decades. CAMEL is one of the important approaches proposed to survey financial performance of banks, which includes five indicators of capital adequacy, assets quality, management quality, earning quality, and liquidity. Therefore, this study aims to assess the influence of CAMEL indicators on banks’ financial performance. In this regard, the study statistical population consists of 14 listed banks on Tehran Stock Exchange during the period 2010_2015. This study has been conducted using a multivariate regression and panel data. The study has one main hypothesis and 5 subsidiary hypotheses. Analysis findings indicated that capital adequacy and assets quality have a significant positive influence on financial performance of banks and liquidity has a significant negative impact on financial performance of banks, while management quality and earning quality indicators has no significant influence on banks’ financial performance. Keywords: Capital adequacy; assets quality; management quality; earnings quality; liquidity quality; bank’s financial performance JEL Classifications: G1, G2